Back Cover: SuFEx‐Based Polysulfonate Formation from Ethenesulfonyl Fluoride–Amine Adducts (Angew. Chem. Int. Ed. 37/2017). Issue 37 (4th July 2017) - Wang, Hua; Zhou, Feng; Ren, Gerui; Zheng, Qinheng; Chen, Hongli; Gao, Bing; Klivansky, Liana; Liu, Yi; Wu, Bin; Xu, Qingfeng; Lu, Jianmei; Sharpless, K. Barry; et al.
Abstract : The sulfur(VI) fluoride exchange (SuFEx)‐based polycondensation reaction between bisalkylsulfonyl fluorides and bisphenol bis( tert ‐butyldimethylsilyl) ethers using [Ph3 P=N−PPh3 ]+[HF2 ] − as the catalyst was been developed. As described by P. Wu, K. B. Sharpless et al. in their Communication onpage 11203 ff., polysulfonates synthesized by this method can be further functionalized using click‐chemistry‐based transformations orthogonal to SuFEx.